INTERFERENSI GRAMATIKAL BAHASA BATAK TOBA PADA KARANGAN NARASI BAHASA INDONESIA SISWA SMA - Fourmey Rindu Marito (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
This study aims to describe: (1) the type of main words and derivative words interference of Batak Toba language in Indonesian narrative essay, (2) the type of interference of the structure of Batak Toba language sentence in Indonesian narrative essay, (3) the causes of Batak Toba interference in Indonesian narrative essay. The method that used in this research is descriptive qualitative method. In this study, the method can give a complete description especially on grammatical interference of Batak Toba languag in Indonesian narrative essay. This research is held at SMA Negeri 1 Simanindo Samosir Regency. The subjects of this research is Xa and Xb class which is about sixty two students. The data is taken from narrative composition which is written by the students. The instrument of this research is the researcher himself. The technique that used in this research is interview technique; it is done to know the students’ background one by one. After knowing sixty two students’ background of SMA Negeri 1 Simanindo Samosir regency, that are from Batak Toba tribe, then the students are assigned to write an article of narration. The result of this research shows that there are two forms of interterence and the factors causing the interference of Batak Toba Language in Indonesian language narrative text, i.e. morphological interference and syntax. As for the forms of interference contained in the narrative essay is the main word and derivative words such as prefixes, suffixes, confix and repetition, while the form of infix is not found. In syntax, interference occurs in the pattern structure of Batak Toba language sentence on the structure of the Indonesian sentence.